(3GdYeOIs - (3Chaj Hf CHj HcQ GdCdabj GdTeThj,J (B1300 (3g` s ((3CMeO Hf eMeO Hf eMeO(B- s)
(3ChdgG (B:s
(3GdMeO ddg GdPi ef HeG HEPfg jRjd YfG GdCdeG Ke GdUdGI hGdSdGe SQeOkG Ydi eMeO eRjd ced OG hBdg hUMHg Chdi GdUaG eG WdH GdfGS ef GdOGA GdTaG s
(3BNQgG (B:s
(3jfJgi HNGJeI jPcQ ajgG eG jLH Ydi GdeYGdL hHYV eG fOH jLH Cf jhUa HGdYOGdI hGdUHQ hGdfUM Hcd MGdI hHGdPcGA hGdJKHJ hCf jYfGO JNaja GdYPGH hGdeDf hCSCd Gddg GdUdGI hGdSdGe Ydi GdfHi hGdBd hUMH GdcQGe YO GdedGFcI hGdQeGd eG GJUa s
(3CQLhRI ai GdWHs
(3eDdagG gh GbOe eDda ehQjJGfi ai GdWH GdHTQi jYQV ddCeQGV GdeYQhaI ai HdOg PGcQkG GdCSHGH hGdCYQGV hebJQMkG GdYdGL ef GdHjfI GdJi jYjT ajgGs
(3hGdcJH GdJi jYJeO YdjgG cJGH GdQMeI ai GdWH hGdMceI deMeO GdegOi Hf EHQGgje GdVHQis
(3GdfSNI HgG MhGT s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
Keywords: (3GdWHs